The Effect of Cucumber Juice (Cucumis sativus L) on Blood Pressure reduction in Pre Hypertension Patients at Oesapa Public Health Center - Agnes Tiara Maharani Dwi Pakaenoni (Cendana Medical Journal, 2025)
ABSTRACT Background: Pre hypertension is a condition where blood pressure is ≥ 130-139/85-89 mmHg, which if ignored may progress to hypertension. Pre hypertension can be prevented through a healthy lifestyle, including non-pharmacological management by consuming cucumber (Cucumis sativus L) juice. Cucumber is a plant commonly found in daily life and contains potassium, which plays role in reducing blood pressure through arteriolar vasodilation mechanisms. Objective: To determine the effect of cucumber juice (Cucumis sativus L) for 7 days, containing 735 mg of potassium or equivalent to 250 ml of cucumber juice, on reducing blood pressure in pre hypertension patients at Oesapa Public Health Center. Method: An intervention study using a one group pre-test post-test design with a total of 15 subjects. The study population consisted of residents in the working area of Oesapa Public Health Center in Kupang City and the sample comprised pre hypertension patients aged 40-59 yaers who agreed to participate in the study. This research was conducted door to door by directly visiting the subjects homes using digital OMRON HBP 1100 sphygmomanometer for 7 days. Results: The Wilcoxon signed ranks test showed significant results between pre test and post test blood pressure with a value of 0.01 for systolic blood pressure and 0.03 for diastolic blood pressure (p<0.05). Conclusion: The administration of cucumber juice (Cucumis sativus L) has an effect on reducing blood pressure in pre hypertension patients at Oesapa Public Health Center. Keywords: Pre hypertension, cucumber, blood pressure.